Tradisi Nyadran Sebagai Sumber Belajar Berbasis Etnopedagogi Di Sekolah Dasar - Indawati, Sulis; Widodo, Wahono; Istiq’faroh, Nurul (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2024)
Primary education plays an important role in shaping students' character, identity, and love for local culture. Ethnopedagogy is an educational approach that incorporates local cultural principles into education, emphasizing the specific values of each culture and fostering students' sense of responsibility for the country's history, language, and traditions. However, ethnopedagogy is still not optimal in elementary school due to problems such as insufficient resources and teaching materials to integrate culture. Nyadran is one of the local cultures of Sidoarjo that can be used as an ethnopedagogy teaching tool in elementary school. This research aims to explore Nyadran as a source of ethnopedagogy learning in elementary school. This research is included in the category of descriptive qualitative research. Data collection techniques with research are used to collect in-depth information from various sources, including through (1) interviews, (2) observations, and (3) documentation studies. The results of the study show that the Nyadran Tradition can be included in the elementary school curriculum as an ethnopedagogy-based learning source that is rich in cultural, philosophical, and social learning values. So it can be concluded that the Nyadran tradition can be used as an ethnopedagogy-based resource to instill cultural values in students from an early age, by linking to subject matter such as social knowledge.